Spartacus - North, Alex 1910-1991 (Universal Pictures Home Entertainment, 2020)
The rebellious Thracian Spartacus, born and raised a slave, is sold to Gladiator trainer Batiatus. After weeks of being trained to kill for the arena, Spartacus turns on his owners and leads the other slaves in rebellion. As the rebels move from town to town, their numbers swell as escaped slaves join their ranks. Under the leadership of Spartacus, they make their way to southern Italy, where they will cross the sea and return to their homes
Based on the novel by Howard Fast
Originally released as a motion picture in 1960
4K Ultra HD Blu-ray details from container
Wide screen (2.20:1)
Bonusmaterial: Ich bin Spartacus: im Gespräch mit Kirk Douglas, Spartacus wiederherstellen, Unveröffentlichte Szenen, Archivinterviews, Ein Blick hinter die Kulissen, Alte Nachrichtensendungen, Bildergalerie, Original-Kinotrailer S
Keywords: Spartacus / -71 B.C. / Drama; Rome / History / Servile Wars, 135-71 B.C. / Drama; Revolutionaries / Rome / Drama; Gladiators / Rome / Drama; Spartacus / -71 B.C. / https://id.oclc.org/worldcat/entity/E39PBJwRXpJX439Tmj6RYTRR8C; Gladiators; Revolutionaries; Rome (Empire); 135-71 B.C.; Film adaptations; Biographical films; Drama; Feature films; Fiction films; Historical films; History; Peplum films; Video recordings for the hearing impaired; Films biographiques; Films historiques; Péplums (Films); Adaptations cinématographiques; Films de fiction; Vidéos pour personnes handicapées auditives; Film; Ultra HD Blu-ray; Blu-Ray-Disc